RED HAT CERTIFIED SPECIALIST IN SERVICES MANAGEMENT AND AUTOMATION EX358 EXAM GUIDE get your certification and prepare for real-world challenges as a Red Hat Certified Specialist - McLeroy, Eric (Packt Publishing Ltd., 2023)
Gain the skills and knowledge to manage your core network services on Red Hat Enterprise Linux with help of self-tests and practical use cases Key Features Get the EX358 certification with this easy-to-follow guide while preparing for real-life challenges Learn everything you need to know about Linux system administration and automation using Ansible 2.9 Use practical use cases and exam-focused questions to prepare for the certification exam Book Description If you're ready to take the next step in your system engineering career with the EX358, then this book is for you. Packed with all the knowledge and skills that you need to configure and maintain services and applications on the Red Hat Linux 8 (RHEL OS 8) platform, this book will help you ace the exam and thrive at work. Red Hat Certified Specialist in Service Management and Automation will help you build a solid foundation of the most recent and up-to-date exam requirements and practice questions. Throughout the course of the book, you'll get hands-on experience with different technical processes needed to fully administer a Red Hat Enterprise Linux 8 system. This will include file storage, database management, direct configuration of applications, such as SMB shares, networking. You'll be well equipped with the configuration of essential components like firewall, SELinux, and iSCSI while learning how to automate these tasks using Ansible Automation 2.9 in order to alleviate the burden of completing them by hand. By the end of this book, you'll have covered all essential topics to ace the Red Hat EX358 certification exam and add another feather to your career as a Red Hat Certified Specialist. What you will learn Attain the skills to take and pass the Red Hat EX358 certification exam Become familiar with the ways of leveraging Ansible Core 2.9 Gain deeper knowledge of the Red Hat Linux Networking with DNS, DHCP, and IP addressing Create your own link and master the networking domain through link aggregation creation Set up printers and email services through Linux servers Get up and running with MariaDB SQL databases Explore how to create and control web traffic Who this book is for This book is for you if you want to advance your career by adding the essential Red Hat certificate to your resume. It will be particularly useful for system administrators responsible for managing large enterprise environments, network services and Red Hat Certified Engineers interested in becoming a Red Hat Certified Architect (RHCA). Before reading this book, you must have a working knowledge of Red Hat Enterprise Linux and Ansible Automation and command line usage of Red Hat Enterprise Linux systems administration.